Yngve Slettholm: Chamber music for saxophone and percussion - Slettholm, Yngve; Lien, Lars; Nystrom, Rolf Erik; Landaas, Vegard; Wilk, Rene (Norway LAWO classics, 2010)
Now, for the first time, Slettholm's complete chamber works for saxophone are available on one recording. This is the first CD release of most of the works. The recordings were made over a period of ten years, and there are strong contrasts in sounds and colourings, from beautiful and tender, to brutal and dominating. "It brings a feeling of acknowledgement knowing that competent performers have taken the initiative to record these six works, which were composed over a period of 20 years and cover a broad spectrum in terms of form and expression. The instrumentation is typically saxophone and percussion in diverse groupings, which could indicate the prevalence of high pressure and powerful outbursts, and which indeed we find in some of the works. But the recording is characterized to a great extent by weaker dynamic range and introspective expression. Tonal concentration is central to most of the works, and the listener is invited to explore the tonal universe of these instruments." - Yngve Slettholm